Stachydrine Ameliorates Cardiac Fibrosis Through Inhibition of Angiotensin II/Transformation Growth Factor β1 Fibrogenic Axis - Liu, Xiao; Shan, Xiaoli; Chen, Huihua; Li, Zan; Zhao, Pei; Zhang, Chen; Guo, Wei; Xu, Ming; Lu, Rong (Frontiers in Pharmacology, 2019)
Cardiovascular diseases, the leading cause of death worldwide, are tightly associated with the pathological myocardial fibrosis. Stachydrine (Sta), a major active compound in Chinese motherwort Leonurus heterophyllus, was reported to effectively attenuate cardiac fibrosis, but the detailed cellular and molecular mechanism remained unclear. In this study, the anti-fibrotic effect and mechanism of Sta were explored in a mouse model of pressure overload and AngII stimulated cardiac fibroblasts (CFs). Mice were randomly divided into sham, transverse aorta constriction (TAC) with saline (TAC+Sal), TAC with telmisartan (TAC+Tel), and TAC with Sta (TAC+Sta) groups. Cardiac morphological and functional changes were evaluated by echocardiography and histological methods, and the molecular alterations were detected by western blotting. Primary cultured neonatal mouse CFs were treated with or without AngII (10-7M) and/or different dosage of Sta (10-6-10-4M) for up to 96 hours, and cell proliferation, cytotoxicity, morphology and related signals were also detected. The in vivo results revealed that TAC prominently induced cardiac dysfunction, left ventricular dilation, myocardial hypertrophy, and elevated myocardial collagen deposition, accompanied with fibrotic markers including α smooth muscle actin (α-SMA) and periostin. However, Sta treatment partially reversed cardiac morphological and functional deteriorations, and significantly blunted cardiac fibrosis as well as Tel. Increments of myocardial angiotensinogen (AGT), angiotensin converting enzyme (ACE), angiotensin II (AngII), AngII type 1 receptor (AT1R), and transformation growth factor β1 (TGFβ1) transcripts after TAC were dramatically down-regulated by Sta treatment. Coincidently, in vitro experiments demonstrated that CFs with AngII stimulation were hyper-activated and trans-differentiated into myocardial fibroblasts (MFs) via up-regulation of AT1R and TGFβ1, evidenced by increased cell proliferation, collagen and fibrotic makers. Meanwhile, Sta potently down-regulated of AT1R and TGFβ1 and thus suppressed those pro-fibrotic effects of AngII in CFs. Moreover, activation of the signals of TGFβ/Smads and TGFβ/MAPKs (mitogen-activated protein kinases) involving in the fibrotic process were observed both in vivo and in vitro cardiac fibrotic models, which were also notably blunted by Sta and Tel as well. Taken together, it was demonstrated in this study that Sta suppressed ACE/AngII/AT1R-TGFβ1 profibrotic axis, and therefore inactivated CFs and blunted MFs transition, which ultimately prevented cardiac fibrosis.